E-022 Outcomes of Aneurysms Embolised with Coils which were Candidates for the Pipeline Flow Diversion Device. (26th July 2014) - Crimmins, M; Banihashemi, A; Gobin, P
Abstract : Introduction: We assessed the outcome of aneurysms which were eligible for treatment using flow diversion device which were treated with detachable coils prior to the adoption of Pipeline. Methods: Data was obtained from a retrospective database of endovascularly Cases were sorted into two groups for this study. Group one consisted of aneurysm with a dome ≥10 mm, aneurysm neck ≥ 4 mm, located in the internal carotid artery and its branches (such as the posterior communicating, anterior choroidal, superior hypophyseal, and ophthalmic arteries), in line with criteria set by the FDA for Pipeline utilization. Group two included cases beyond the FDA indication but within institutionally accepted usage criteria (aneurysms of any size located on the side wall of the branches of the carotid artery or middle cerebral (M1), basilar, vertebral and posterior cerebral artery, with an aneurysm neck ≥3 mm or a dome-to-neck-ratio < 1.5, no limits were placed on dome size). Exclusion for either group was a history of aneurysm rupture or previous neurosurgical procedures. Results: Only 50% of the FDA group could be completely embolised with 27% requiring retreatment. 53% of institutional criteria patients were completely embolised with an 8.7% retreatment rate. Characteristics of the patients and aneurysms with the outcome of the procedure, both immediate and longer term outcome will be presented. The time from initial endovascular operation to re-treatment by endovascular means at our institution in the 12 cases requiring re-treatment was 12.4 ± 14.0 months. Conclusion: Cases that met FDA criteria were significantly more likely to require recoiling than institutional criteria. Aneurysms that meet FDA or institutional criteria for a flow diverting stent are difficult to treat, often incompletely embolised with coiling alone and often need more than one embolization procedure. We present our experience with coil embolization in aneurysms that could have been treated with Pipeline flow diverter. Disclosures: M. Crimmins: None. A. Banihashemi: None. P. Gobin: None.